Income Models, Book Yield, and the Rate of Return. - Vatter, William J. (The Accounting Review, 1966)
The article focuses on the significant advances in accounting for income models, book yield and the rate of return of companies. The author considers the characteristics of the compound-interest investment model. He also explains the apparent differences between book yield and the project rate of return. The underlying difference is that the project rate and the book yield are calculated under two different sets of conditions, and with two purposes in mind. In addition, the author observes that many of the problems that arise in the use of book yields stem from the attempt to oversimplify the given situation.